HRM Practices in Nepalese Public Financial Institutions - Basnet, Bhupindra Jung; Timilsina, Jagat; Risal, Nischal (NCC Journal, 2024)
The aim was to assess the role of HRM practices in Nepalese public financial institutions. The research design was descriptive. The mean was used to describe the position of HRM practices. The result was that performance-related reward, performance appraisal, training and development, empowerment, selection, and communication were properly practiced in Nepalese public financial institutions; HRM practices were properly used in Nepalese public financial institutions. Selection, communication, training and development, performance appraisal, performance-related reward, and empowerment have been adequately used in Nepalese public financial institutions. HRM practices have been satisfactorily used in Nepalese public financial institutions.